Biosecurity for the boarding of Medicine Hospital from Trujillo - La Libertad 2010: report of the death of a medical students - Galán-Rodas, Edén (2010)
Objectives: To know the features of medicine internship in the main hospitals directed by the Ministry of Health (MINSA) and Peruvian Social Security (EsSalud) in La Libertad, Trujillo.   Material and Method: We performed a cross sectional study in a sample of 80 internal medicine Hospital Trujillo - La Libertad during the months of July-August 2010, using as the survey study "Characteristics of Medicine Internship in Peru, 2010 ". Descriptive statistics with absolute and relative frequencies.   Results: Eighty medicine interns were interviewed, 61,2% (49) were male and 38.8 (31) were female, and their ages were between 23 and 27 years. Forty percent had training about biosafety; however, none received any technical documents regarding this topic. Some interns declared they had an insurance policy for working place-related accidents and adequate places for rest (13,7% and 17,5%, respectively).   Conclusion: Interns lack appropriate and timely training in biosafety issues, and these persons are exposed to a great deal of risk during their last year of medical training in the hospital, and the great majority of them do not have any insurance policy that may protect them from working place-related accidents.